1999
DOI: 10.1002/(sici)1096-8628(19990604)84:4<373::aid-ajmg13>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterotaxy-neural tube defect and holoprosencephaly occurring independently in two sib fetuses

Abstract: We report on two sib fetuses, products of a consanguineous union, who had multiple and apparently unrelated malformations. The first fetus, a female, had trilobed lungs, a single cardiac ventricle, asplenia, situs ambiguus of the liver, and a lumbosacral meningomyelocele. The brain of this fetus was normal. The second fetus, a male, had bilobed lungs, a single cardiac ventricle, situs solitus of the abdominal organs and spleen, and a semilobar holoprosencephaly. The occurrence of these malformations in sibs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Neurologic abnormalities are known to be part of heterotaxy, although the associations are not completely understood. Agenesis of the corpus callosum, holoprosencephaly, myelomeningocele, and neural tube defects have been reported [ 45 - 46 ]. Such associations were also found in the mouse model of heterotaxy [ 47 ].…”
Section: Reviewmentioning
confidence: 99%
“…Neurologic abnormalities are known to be part of heterotaxy, although the associations are not completely understood. Agenesis of the corpus callosum, holoprosencephaly, myelomeningocele, and neural tube defects have been reported [ 45 - 46 ]. Such associations were also found in the mouse model of heterotaxy [ 47 ].…”
Section: Reviewmentioning
confidence: 99%
“…The association between holoprosencephaly microforms and situs inversus has been described previously (30), indicating that the same gene may be responsible for heterotaxy and midline defects. None of the reported patients with such an association have circumferential skin folds.…”
Section: Discussionmentioning
confidence: 55%
“…Congenital absence of the spleen is usually accompanied by complex cardiac malformations, malposition and maldevelopment of the abdominal organs, and abnormal lobation of the lungs and configures the Ivemark syndrome in which an autosomal recessive inheritance was supposed. Moreover, Bonneau et al 5 reported two sib fetuses, products of a consanguineous union, who had multiple and apparently unrelated malformations. The first fetus, a female, had trilobed lungs, a single cardiac ventricle, asplenia, situs ambiguus of the liver, and a lumbosacral meningomyelocele.…”
Section: Discussionmentioning
confidence: 99%